2007
DOI: 10.1186/1471-2105-8-5
|View full text |Cite
|
Sign up to set email alerts
|

Discovering biomarkers from gene expression data for predicting cancer subgroups using neural networks and relational fuzzy clustering

Abstract: Background: The four heterogeneous childhood cancers, neuroblastoma, non-Hodgkin lymphoma, rhabdomyosarcoma, and Ewing sarcoma present a similar histology of small round blue cell tumor (SRBCT) and thus often leads to misdiagnosis. Identification of biomarkers for distinguishing these cancers is a well studied problem. Existing methods typically evaluate each gene separately and do not take into account the nonlinear interaction between genes and the tools that are used to design the diagnostic prediction syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 28 publications
(50 reference statements)
2
48
0
2
Order By: Relevance
“…These genes are listed in Table 1. Note that these 20 genes have many redundant genes as reported in [22].…”
Section: B Initial Dimensionality Reduction With Neural Networkmentioning
confidence: 92%
See 3 more Smart Citations
“…These genes are listed in Table 1. Note that these 20 genes have many redundant genes as reported in [22].…”
Section: B Initial Dimensionality Reduction With Neural Networkmentioning
confidence: 92%
“…At the beginning of training, these gates are kept almost closed, and the training algorithm opens the required gates (allows features to enter the network) depending on the ability of features to reduce the training error. The same set of twenty genes selected by FSMLP in [22] are used here. These genes are listed in Table 1.…”
Section: B Initial Dimensionality Reduction With Neural Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Pal et al proposed a scheme that integrated neural network classifiers and fuzzy clustering for identifying a small set of biomarkers to distinguish four usually misdiagnosed childhood cancers. They have shown that their approach was capable of identifying a very small set of genes as biomarkers with high performance, by taking the interaction between genes into consideration [49]. In another study, Chambwe et al performed unsupervised hierarchical clustering on genome-wide DNA methylation data of 140 DLBCL samples and ten normal germinal center B cells.…”
Section: Bioinformatics and Biostatistics In Mining Epigenetic Biomarmentioning
confidence: 98%